Imbalance in amino acid and purine metabolisms at the hypothalamus in inflammation-associated depression by GC-MS. Issue 12 (13th November 2017) - Wu, Yu; Li, Yonghong; Jia, Yanjuan; Wei, Chaojun; Xu, Hui; Guo, Rui; Li, Yuanting; Jia, Jing; Qi, Xiaoming; Gao, Xiaoling
Abstract : Imbalances of amino acids and the purinergic system show significant hypothalamic metabolic perturbations, which are closely associated with mechanisms of depression. Abstract : Hypothalamic dysfunction is a key factor in depression; increasing evidence highlights neuroinflammation abnormalities as well as imbalances in neurotransmitters and the purinergic system in the pathophysiology of depression. However, little is known about the metabolomic changes in the hypothalamus of depressed patients with neuroinflammation. Herein, taking advantage of the well-established lipopolysaccharide (LPS)-induced depression mouse model, we measured metabolic changes in the hypothalamus using gas chromatography-mass spectrometry (GC-MS). Sucrose preference test (SPT), open field test (OFT), forced swimming test (FST), and tail suspension test (TST) were conducted to assess our depressive model. To better understand the metabolic disturbances occurring in the hypothalamus of depressed mice, multivariate statistics were applied to analyse the clinical significance of differentially expressed metabolites in the hypothalamus of mice with LPS-induced depression. Bioinformatic analysis was conducted to detect potential relationships among the changed metabolites. The data confirmed that mice with LPS-induced depression were good mimics of depression patients in some characteristic symptoms such as decreased sucrose intake and increased immobility. In our study, 27 differentially expressed metabolites were identified in the hypothalamus of mice with LPS-induced depression. Herein, seventeen of these metabolites decreased, whereas 10 metabolites increased. These molecular changes were closely related to perturbations in the amino acid and purine metabolisms. Our data indicate that dysfunction of amino acid and purine metabolisms is one of main characteristics of inflammation-mediated depression. These results provide new insights into the mechanisms underlying depression, which may shed some light on the role of the hypothalamus in the pathogenesis of inflammation-mediated depression.